Self-Organization of Gold Nanoparticle Assemblies with 3D Spatial Order and Their External Stimuli Responsiveness - Serrano, Melissa S. Koehn; Koenig, Tobias A. F.; Haataja, Johannes S.; Lobling, Tina I.; Schmalz, Holger; Agarwal, Seema; Fery, Andreas; Greiner, Andreas (Macromolecular Rapid Communications, 2016)
Gold nanoparticles (AuNP) with pyridyl end-capped polystyrenes (PS-4VP) as "quasi-monodentate" ligands self-assemble into ordered PS-4VP/AuNP nanostructures with 3D hexagonal spatial order in the dried solid state. The key for the formation of these ordered structures is the modulation of the ratio AuNP versus ligands, which proves the importance of ligand design and quantity for the preparation of novel ordered polymer/metal nanoparticle conjugates. Although the assemblies of PS-4VP/AuNP in dispersion lack in high dimensional order, strong plasmonic interactions are observed due to close contact of AuNP. Applying temperature as an external stimulus allows the reversible distortion of plasmonic interactions within the AuNP nanocomposite structures, which can be observed directly by naked eye. The modulation of the macroscopic optical properties accompanied by this structural distortion of plasmonic interaction opens up very interesting sensoric applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: gold nanoparticles; nanostructures; self-assembly; sensors